2000
DOI: 10.1177/0739986300221004
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and Gender Differences in Moral Judgment: A Study of Mexican Americans and Anglo-Americans

Abstract: Kohlberg's theory of moral development regards justice concerns as developmentally more advanced than interpersonal considerations. Men tend to score as more morally developed than women on existing measures. Gilligan suggested that this is because women rely more on "care" considerations in moral dilemmas, whereas men rely more on "justice" issues. Snarey noted similar bias in the cross-cultural realm. The authors studied moral judgment in Mexican American (n = 40) and Anglo-American (n = 40) college students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
(50 reference statements)
0
14
1
5
Order By: Relevance
“…As a man, one should have the spirit of 'loving others as loving yourself.' (Ma, 1988b, p. 214) Empirical research seems to confirm that the post-conventional moral reasoning of people from collectivist cultures, like South Asians (Miller and Bersoff, 1992) and Mexican Americans (Gump et al, 2000), tends to be relationship based, while the moral reasoning of people from more individualist cultures tends to be justice based.…”
Section: Moral Judgmentmentioning
confidence: 95%
“…As a man, one should have the spirit of 'loving others as loving yourself.' (Ma, 1988b, p. 214) Empirical research seems to confirm that the post-conventional moral reasoning of people from collectivist cultures, like South Asians (Miller and Bersoff, 1992) and Mexican Americans (Gump et al, 2000), tends to be relationship based, while the moral reasoning of people from more individualist cultures tends to be justice based.…”
Section: Moral Judgmentmentioning
confidence: 95%
“…These differences led Gilligan to describe two divergent modes of moral reasoning: an ethic of care and an ethic of justice (Gump et al 2000). Other studies confirmed these differences in various tests for evaluating moral judgment (Aldrich and Kage 2003;Bjorklund 2003;Eisenman 1967;Gump et al 2000;Indick et al 2000;Skoe 1995). Despite these reports, others found no gender differences (Brabeck and Shore 2003;Jaffee and Hyde 2000;Keasey 1972;Lifton 1985;McGraw and Bloomfield 1987), leaving this topic open to debate.…”
Section: Introductionmentioning
confidence: 92%
“…Whereas men solve moral dilemmas in a rational way, respecting law and order, women are driven by emotion, empathy and care for others. These differences led Gilligan to describe two divergent modes of moral reasoning: an ethic of care and an ethic of justice (Gump et al 2000). Other studies confirmed these differences in various tests for evaluating moral judgment (Aldrich and Kage 2003;Bjorklund 2003;Eisenman 1967;Gump et al 2000;Indick et al 2000;Skoe 1995).…”
Section: Introductionmentioning
confidence: 92%
“…Segundo Brown (1984), o termo -valor‖ denota preferência em termos de escolha de uma coisa em detrimento de outra por uma noção de que uma é melhor que a em que o raciocínio moral leva em conta não mais a regra, mas os princípios morais universais de justiça e equidade sobre os quais as regras são construídas (GUMP et al, 2000;KARPIAK & BARIL, 2008, SHERBLOM, 2008.…”
Section: Valores E Garantias: Valores De Justiça X Valores De Cuidadounclassified
“…Não menos importantes são as críticas feitas à sua teoria. Uma das mais destacadas objeções acusa Kohlberg de etnocentrismo e de generalização imprópria, já que seus princípios e valores universais de justiça, importantes na definição dos últimos estágios de moralidade, seriam representativos apenas de amostras compostas de indivíduos do sexo masculino, anglo-americanos e brancos (GUMP et al, 2000). Além disso, para muitos autores, ao focar sua atenção no papel da cognição para o desenvolvimento moral, Kohlberg teria negligenciado outras dimensões morais, como o afeto e a intuição (MORTON et al, 2006;HAIDT, 2001).…”
Section: Valores E Garantias: Valores De Justiça X Valores De Cuidadounclassified